Analyzing the impact of existing floor price on the brokerage industry: a case study of LankaBangla Securities - Khan, Redwan Alam (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.